THE ROLE OF THE «KIFAYA» WORK IN EDUCATING YOUTH ON THE BASIS OF PURE ISLAMIC ENLIGHTENMENT IN NEW UZBEKISTAN (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the issue of educating youth on the basis of pure Islamic enlightenment in the context of New Uzbekistan and the role of the «Kifaya» work in this process. The jurisprudential, ethical, and enlightenment dimensions of the work are examined, and its potential in forming moderate religious views among young people is highlighted. The necessity of harmonizing the classical source with modern pedagogical approaches is also discussed. The conclusion substantiates that the «Kifaya» work, when applied through proper methodology, can serve as an effective tool in youth education.
Keywords: New Uzbekistan; youth education; Islamic enlightenment; «Kifaya» work; jurisprudence; religious consciousness